Dysphagia due to spontaneous hyperinflation of a swallowable intragastric balloon. Issue 6 (24th June 2021) - Gaunt, Elizabeth Ann; Fernandes, Roland
Abstract : A 49-year-old woman presented as an acute admission with persistent vomiting and an inability to tolerate both solids and liquids. Five weeks prior to the admission she had an Elipse swallowable intragastric balloon placed into her stomach as an aid to weight loss. This type of balloon stays inflated inside the stomach for 16 weeks before disintegrating and passing through the gastrointestinal tract. Observations and blood parameters were unremarkable but abdominal radiograph indicated that the balloon had undergone spontaneous hyperinflation—a rare complication. At gastroscopy, the balloon was found to fill the entire stomach volume causing dysphagia. The balloon was punctured endoscopically, contents suctioned and remnants retrieved through the gastroscope. The patient commenced oral intake the following day and was discharged home with no further symptoms at 12-week follow-up.